PENGARUH KOMPETENSI DOSEN DAN KINERJA DOSEN TERHADAP MOTIVASI BELAJAR MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS ISLAM MALANG - Febytria Nur Imawati; Abdul Kodir Djaelani; Khalikusabir Khalikusabir (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThe purpose of this studi was to determine the effect of lecturer competence and lecturer performance on learning motivation, the research is done at university with the Faculty of Economic and Business student respondents at University of Islam Malang. The population in this all student of the Faculty of Economic and Business of Malang Islamic University majoring in management who have taken courses in Ismamic Economics with a total of 563 students. Determination of the sample in this study using the Slovin formula of 85 students. Primary data obtained from the results of respondents answers on the questionnaire distributed while secondary data obtained from the administration (TU) of the Faculty of Economics and Business, University of Islam Malang. Data analysis method uses liniear regression and coefficient of determination. The results showed that the competence of lecturers had a significant effecton student motivation in the Faulty of Economics and Business, while the perfomance of lecturers has no effect and is not significant on student motivation in the Faulty of Economics and Business Univerrsity of Islam Malang.